Bisphosphonate-Induced Osteonecrosis of the Jaw: Case Report - Caldas, Rogério Jardim (2009)
The jaws osteonecrosis induced by bisphosphonates is the first late complication of therapy with bisphosphonates described in scientific literature. This is defined as the development of necrotic bone in the oral cavity of a patient who is receiving treatment with bisphosphonates and did not receive radiotherapy in the head or neck region. Clinically, the lesions are characterized as ulceration of the oral mucosa, which is often very painful, and exposes the underlying bone. This paper reports a case of osteonecrosis induced by bisphosphonates of spontaneous surging, difficult to respond to conservative treatment, then achieving a cure with surgery.